The effect of fibod smart balance with "endless run" game in improving memory and attention in healthy young adults : an eye tracking study - A/P Govindan, Inthu Jaa (2021)
RESULTS: The statistical test of repeated measure ANOVA showed that there was no significant difference in response accuracy (F (1,32) = 3.17, p = 0.085, ηp2 = 0.09) and reaction time (F (1,32) = 0.03, p = 0.856, ηp2 = 0.001) of working memory after FIBOD smart balance training. There was also no significant difference in response accuracy (F (1,32) = 3.13, p = 0.087, ηp2 = 0.09) of visual attention however there was a significant difference in reaction time (F (1,32) = 4.52, p = 0.041, ηp2 = 0.12) of visual attention after FIBOD smart balance training thus a planned comparison using paired samples t-tests, revealed that the experimental group showed a significant difference [mean difference = 48.35, 95 % CI = (19.68, 77.03)], p = 0.003 in the reaction time. CONCLUSION: FIBOD smart balance training can be regarded as an effective balance-based exergame for improving visual attention in healthy young adults.